Functional polyester with widely tunable mechanical properties: The role of reversible cross-linking and crystallization. (18th May 2015) - Kuang, Xiao; Liu, Guoming; Zheng, Liuchun; Li, Chuncheng; Wang, Dujin
Abstract: A novel strategy for preparation of unsaturated polyester-based functional materials with widely tunable mechanical properties has been reported in present work. The biodegradable and crystallizable poly(butylene fumarate) oligomer (PBF) bearing reactive carbon–carbon double bonds on the backbone was functionalized by Michael addition with furfurylamine (FA), followed by incorporating bismaleimide (BMI) as cross-linker to form a reversibly cross-linked polyester (PBF-FA-BMI). The obtained material was systematically characterized by a combination of differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), rheometry measurement, wide-angle X-ray scattering (WAXS) as well as mechanical property testing. The in-situ FTIR and rheology measurements demonstrated the competition process of DA reaction and crystallization for dynamic conditions and isothermal conditions. The characteristic of dynamically chemical structure variation and crystallization behavior provides a possibility to tune the mechanical property of PBF-FA-BMI. By thermal treatment, the structure programming of the material can be facilely achieved, which undergoes from a typically elastomer to plastic. A schematic illustration of thermo-responsive conversion and recyclability is proposed for the cross-linked polyester. Graphical abstract: Highlights: Unsaturated biodegradable poly(butylene fumarate) was functionalized by Michael addition. Fast reversibly cross-linked polyester was prepared by Diels–Alder reaction. Competition between cross-linking reaction and crystallization was controlled by thermal treatment. Mechanical properties were widely tunable from elastomer to plastic.